Long-term treatment with fibrates and ursodeoxycholic acid in people with Primary Sclerosing Cholangitis is safe and associated with persistent clinical and biochemical improvement. (March 2023) - Catanzaro, E.; Peviani, M.; Perin, N.; Bonaiuto, E.; Simionato, F.; Motta, R.; Gambato, M.; Floreani, A.; Cazzagon, N.
Abstract : Introduction: People with Primary Sclerosing Cholangitis(PSC) have no effective medical treatment for delaying disease progression. Ursodeoxycholic acid(UDCA) improves liver tests(LFTs) and prognostic markers. Fibrates, PPARs agonists, are recommended as first-line therapy for pruritus in PSC. However, long-term data on safety and effectiveness of fibrates on pruritus, LFTs and prognostic markers in PSC are lacking. Aim: To assess long-term safety and effectiveness of fibrates in PSC. Methods: Retrospectively, we collected data of PSC people treated with fenofibrate (200 mg/day) or bezafibrate (400 mg/day) for at least 6 months in addition to UDCA, for persistent alkaline phosphatase (ALP) elevation (>1.5xULN), pruritus or dyslipidemia. Changes in LFTs, liver stiffness by VCTE, symptoms, prognostic scores and occurrence of adverse events every 6 months after fibrates introduction were collected. Results: Twenty-seven consecutive PSC people who started fibrates (fenofibrate n=25, bezafibrate n=2) between 2017 and 2020 were included. Median age at diagnosis was 31(21-35). Upon treatment with fibrates (median duration of 33.3[20.8-51.2] months), we observed a significant reduction of ALP, GGT and transaminases. A decrease of ALP levels of 41%, 52%, 46%, 54% at 6, 12, 18, 24 months compared to baseline values, respectively, was observed. Nearly a third of people achieved ALP normalization at semestral evaluations. The Amsterdam-Oxford score significantly improved after 12 months (1.75 vs. 1.35, p=0.03). Liver stiffness showed a non-significant reduction on long-term. Number of patients experiencing pruritus significantly decreased at each time point, as well as fatigue at 18 months (p=0.03). One third of people interrupted fibrates for non-response, but no adverse events related to fibrate treatment occurred during follow-up. Conclusions: Long-term combination of fibrates and UDCA in people with PSC is safe and associated with persistent clinical and biochemical improvement. While awaiting the results of ongoing phase 3 study, we consider fibrates as a valid therapeutic option in people with PSC and elevated liver tests despite UDCA.